2019
DOI: 10.1002/ijgo.13051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a structured educational package on women's sexual function during pregnancy

Abstract: ObjectiveTo explore the effect of a structured educational package based on ADDIE (analysis, design, development, implementation, evaluation) to reduce sexual dysfunction during pregnancy.MethodsA randomized controlled trial study among pregnant women attending prenatal clinics in Tehran, Iran, from October 2017 to September 2018. The implementation group received the structured educational package; the control group received training on breastfeeding and normal delivery. The outcome measure was changes in tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…Changes in sexual function may interfere with sexual practices and positions adopted during pregnancy (3) . Thus, there is a need to strengthen the effective implementation of sexual and reproductive health actions in Primary Health Care (23) , since sex education carried out in prenatal care by trained professionals contributes to improve sexual response and promote adaptive behaviors (24) .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in sexual function may interfere with sexual practices and positions adopted during pregnancy (3) . Thus, there is a need to strengthen the effective implementation of sexual and reproductive health actions in Primary Health Care (23) , since sex education carried out in prenatal care by trained professionals contributes to improve sexual response and promote adaptive behaviors (24) .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the mean score of sexual function was similar in both intervention groups of couples and pregnant women, and the face-to-face training of pregnant women, even in the absence of their husbands, as well as the training of couples, increased the sexual function of pregnant women [ 30 , 31 ]. Nejati et al [ 32 ] and Ismaili et al [ 33 ] found a significant difference between the mean score of sexual function in both their control and case groups 4 weeks after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…in 2020, sexual counseling significantly increased the score of couples’ sexual function and most of its aspects. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] In a study that was conducted in Qazvin in 2019 by Mahnaz et al ., results indicated that structures education in the form of speech based on an accurately scheduled plan, activity plan, determining the activities, and determining the educational content could improve sexual performance. [ 23 ]…”
Section: Introductionmentioning
confidence: 99%